2006
DOI: 10.1593/neo.05832
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Effect of Inhibition of the Ubiquitin-Conjugating Enzyme E2C on Esophageal Adenocarcinoma

Abstract: Ubiquitin-dependent proteolysis of cyclins plays a critical role in cell cycle progression and tumorigenesis. We examined the expression of ubiquitin-conjugating enzyme E2C (UBE2C) during progression from Barrett's metaplasia to esophageal adenocarcinoma (EA) and the effects of targeting this enzyme on EA-derived cell lines. Using oligonucleotide microarrays UBE2C expression was elevated in 73% (11 of 15) of EAs relative to Barrett's metaplasia. Tissue microarray showed elevated UBE2C in 70% (7 of 10) of dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
7
45
0
Order By: Relevance
“…Similar paradoxical direct associations between UBE2C and cyclin B1 have been reported in lymphomas. 33 Although no specific UBE2C inhibitors are currently available for clinical use, Lin et al 10 have shown that treatment of esophageal adenocarcinoma cells with MG-262, a proteasome inhibitor, caused a significant downregulation of UBE2C accompanied by inhibition in cell proliferation and accumulation of cyclin A and B1. We have recently shown that bortezomib, another proteasome inhibitor, suppressed the growth and reduced cell viability in a number of cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar paradoxical direct associations between UBE2C and cyclin B1 have been reported in lymphomas. 33 Although no specific UBE2C inhibitors are currently available for clinical use, Lin et al 10 have shown that treatment of esophageal adenocarcinoma cells with MG-262, a proteasome inhibitor, caused a significant downregulation of UBE2C accompanied by inhibition in cell proliferation and accumulation of cyclin A and B1. We have recently shown that bortezomib, another proteasome inhibitor, suppressed the growth and reduced cell viability in a number of cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with an earlier study in which esophageal adenocarcinoma cells strongly expressing UbcH10 were highly sensitive to treatment with the proteasome inhibitor MG-262. 10 Results of previous bortezomib clinical trials either alone or in combination (oxaliplatin, leucovorin, and 5-fluorouracil with fluorouracil/leucovorin or irinotecan) in the setting of advanced CRC are not encouraging. [35][36][37] However, using bortezomib in combination with other biological agents through an understanding of its effects on different signaling pathways may prove more fruitful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ubiquitin-conjugating enzyme E2C (UBE2C) belongs to the E2 family, and is involved in mitotic cyclin destruction and cell cycle progression (8). UBE2C has been implicated in the carcinogenesis of certain tumors (9,10), and is overexpressed in various human cancers, including breast, esophageal, colon, lung, liver and ovarian cancers (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%